Strategi Engineering Design Process (EDP) Terintegrasi PjBL-STEM dalam Program Pembelajaran: Analisis Kebutuhan untuk Merangsang Keterampilan Literasi Numerasi pada Topik Energi Terbarukan - Sofhia Chairunnisya; Abdurrahman; I Wayan Distrik; Kartini Herlina; Undang Rosidin; Ghani Fadhil Rabbani (Jurnal Penelitian Pendidikan IPA, 2023)
This research constitutes a preliminary study aimed at determining the needs of teachers and students in the learning process, particularly in the context of physics subjects related to renewable energy. The chosen research method is a survey, conducted among 27 physics teachers and 59 high school students in MIPA field in Lampung Province using Google Forms. The collected data is then curated and analyzed to identify and address these educational needs. The results of the data analysis reveal a demand for learning programs that can enhance students' numeracy and literacy skills during the learning process. According to the survey, only 43% of teachers and 24% of high school students majoring in Mathematics and Natural Sciences are aware of the Sustainable Development Goals (SDGs). This aligns with the finding that only 40% of teachers have integrated PjBL-STEM into their learning programs. The worksheets lack activities that can stimulate students' numeracy and literacy skills, thereby impeding their active engagement in renewable energy learning. These findings are further corroborated by student questionnaires, which indicate that 55% of students feel they face limitations in understanding materials related to renewable energy. Additionally, 85% of physics teachers express concerns about students' difficulties in grasping the concept of renewable energy. Consequently, the development of an integrated renewable energy learning program incorporating PjBL-STEM becomes imperative.